Characterization of ZnWO4, MgWO4, and CaWO4 Ceramics Synthesized in the Field of a Powerful Radiation Flux; Ceramics; Vol. 7, iss. 3 - Alpysova G. K. Gulnur Kenzhebekovna; Lisitsyn V. M. Viktor Mikhailovich; Bakieva Zh. Zhanara; Chakin I. K. Ivan Konstantinovich; Kaneva E. V. Ekaterina Vladimirovna; Afanasjev D. A. Dmitry Aleksandrovich; Tusupbekova A. K. Aynura Kairzhanovna; Vaganov V. A. Vitalii Andreevich; Tulegenova A. T. Aida Tulegenkyzy; Tuleuov C. (2024, 2024)
Title screen